Letter (copy) : Spain - Citrine, Walter, 1887-1983
021-0064-001 WMC/WJB/AC/594 International 25th March, 1937 Mr. W. Elger, Scottish Trades Union Congress General Council, 33, Elmbank Crescent. GLASGOW, C.3. Dear Mr. Elger, SPAIN. In reply to your letter of 23rd instant, we sent to you a copy of the I.F.T.U. "Bulletin" of 17th March, which contains an account of the recent Joint International Conference with the decisions. Since then the General Council have seen Mr. Eden, the Foreign Secretary, and yesterday they passed a resolution. You will probably have seen in the "Daily Herald" references to this matter. Yours faithfully, General Secretary. 292/946/21/64